MENTORING PROGRAM FOR THE IMPLEMENTATION OF THE LEARNING EVALUATION MODEL IN THE INDEPENDENT CURRICULUM AT SMA 2 GUNUNG TALANG SOLOK DISTRICT - Yenni Melia; Waza Karia Akbar; Erningsih Erningsih; M Arifin; Elvawati Elvawati; Irwan Irwan (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2023)
Learning evaluation is carried out so that at each stage in the learning process we can see the strengths and weaknesses that a student has gone through, if the desired results occur then remediation or repetition of the material can be carried out. There are also differences between independent curriculum learning evaluations and curriculum 13, namely: 1) National Standard School Examinations, developed by each school, 2) National Examinations changed to minimum competency assessments and character surveys, 3) freedom of educators to design Learning Implementation Plans (RPPs). ) and 4) flexibility in accepting students.